The Effectiveness Of Fishbone Method On Students’ Writing Ability Of Argumentative Text - Fauziah, Meli (LENTERNAL: Learning and Teaching Journal, 2022)
This research departed from some problems faced by senior high school students in writing argumentative text such as their difficulties to organize the idea, lack of intention in writing, and lack of technique especially in writing argumentative text. The objective of this research was to find out whether the use of fishbone diagram could improve students’ ability in writing argumentative text or not. This research was a classroom action research. The subject of this research was 34 students consisted of 12 males and 22 females. The instruments of this research were writing test, students’ and teacher’s observation checklist, and interview. The research was conducted in two cycles which included plan, action, observation, and reflection. The result of this research showed that there was an improvement of students’ ability in writing argumentative text in every cycle. In the pre-test, the students’ mean score was 58.2. In cycle 1, the students’ mean score was 66.7. In the cycle 2, the mean score of the students was 77.7. It could be revealed that fishbone diagram was effective in improving students’ ability in writing argumentative text.